Metal-graphene hybrid active chiral metasurfaces for dynamic terahertz wavefront modulation and near field imaging. (15th August 2020) - Li, Jie; Li, Jitao; Yang, Yue; Li, Jining; Zhang, Yating; Wu, Liang; Zhang, Zhang; Yang, Maosheng; Zheng, Chenglong; Li, Jiahui; Huang, Jin; Li, Fuyu; et al.
Abstract: Chiral metasurfaces can achieve giant chiral optical responses and have been expanded from the optical band to other electromagnetic bands. Here, we propose a new method for dynamic terahertz circular dichroism (CD) manipulation in metasurfaces. By introducing a patterned and electrically doped graphene into the metamirror consists of double layer C-shaped split ring resonators (SRRs), efficient terahertz CD modulation is observed. Since the electrical doping of graphene changes the absorption loss of the metasuface cavity, the structure shows switching between a chiral metasurface and an ordinary metal mirror, which can be seen as "on" and "off" states. The calculation results show an efficient modulation of the terahertz CD in a large dynamic range. In addition, we also use the new method to design two metasurfaces for dynamic terahertz wavefront modulation and near-field digital imaging, both of which show a high-performance electrical switching. This method provides a new way for the design of active terahertz devices based on metasurfaces, and also promotes the applications of terahertz chiral metasurfaces in high-speed wireless communication and dynamic imaging. Graphical abstract: Image 1